Effect of Multi-sensory Stimulation on Neuromuscular Development of Premature Infants - Zeraati, Hossein; Nasimi, fatemeh; Shahinfar, Javad; ghorban zadeh, maryam (Iranian Journal of Child Neurology, 2018)
Background: preterm birth is considered as a risk factor for developmental disabilities, which can lead to long-term effects on the nervous system of children. Objectives: The aim of this study was to determine the effect of multi-sensory stimulation on neurodevelopment of premature infants. Materials & Methods: In this two-group double-blind clinical trial conducted from June to August 2016 in Iran, 80 preterm infants were randomly divided into two groups. The Intervention group received multisensory stimulation for 12 min per session, 5 sessions per wk along with routine NICU care the control group received ward’s routine care. Neuromuscular Maturity each infant was assessed by New Ballard Score. Results: The intervention group showed higher Neuromuscular Maturity compared to the control group. The Posture, Arm Recoil, Popliteal angle and Heel to ear were statistically significant between the groups. Conclusions: The results shows that Multi-sensory stimulation can have beneficial effects on the development of neuromuscular in premature infants. Keyword: Multisensory stimulation. Neurodevelopmen. premature infants